2022
DOI: 10.1186/s12915-022-01321-3
|View full text |Cite
|
Sign up to set email alerts
|

Ileum tissue single-cell mRNA sequencing elucidates the cellular architecture of pathophysiological changes associated with weaning in piglets

Abstract: Background In mammals, transitioning from sole milk uptake to the intake of solid feed results in dramatic developmental changes in intestinal function and immunological status. In fact, weaning stress is often accompanied by intestinal inflammatory processes. To develop effective intervention strategies, it is necessary to characterize the developmental pattern and immune response that occurs on weaning, as we have done in this study for piglets. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 71 publications
(79 reference statements)
0
7
0
Order By: Relevance
“…-Human intestinal physiology, nutrition, and microbiota more similar to pigs than mice (188)(189)(190)(191)(192)(193)(194) -Proportions of gdTCR T-IELs, CD8ab + abTCR T-IELs, and CD8aa + abTCR T-IELs in human intestine more similar to pigs than mice (1,7,25,29,66,67,(195)(196)(197) -Transcriptional similarities between human and porcine intestinal immune and epithelial cells identified via high-resolution transcriptomics (57,(198)(199)(200) -Biomedical applications using pig models have cross-utility to improve pig health and global food security Frontiers in Immunology frontiersin.org assess transcriptomes of epithelial cells in duodenum, jejunum, and ileum of the porcine small intestine, finding again transcriptional similarities between humans and pigs for the majority of epithelial cells (200). Thus, high-resolution transcriptomic analyses support transcriptional conservation between immune and epithelial cells of human and porcine intestine, but scRNA-seq studies have so far been limited to only the small intestine.…”
Section: Advantagesmentioning
confidence: 99%
See 1 more Smart Citation
“…-Human intestinal physiology, nutrition, and microbiota more similar to pigs than mice (188)(189)(190)(191)(192)(193)(194) -Proportions of gdTCR T-IELs, CD8ab + abTCR T-IELs, and CD8aa + abTCR T-IELs in human intestine more similar to pigs than mice (1,7,25,29,66,67,(195)(196)(197) -Transcriptional similarities between human and porcine intestinal immune and epithelial cells identified via high-resolution transcriptomics (57,(198)(199)(200) -Biomedical applications using pig models have cross-utility to improve pig health and global food security Frontiers in Immunology frontiersin.org assess transcriptomes of epithelial cells in duodenum, jejunum, and ileum of the porcine small intestine, finding again transcriptional similarities between humans and pigs for the majority of epithelial cells (200). Thus, high-resolution transcriptomic analyses support transcriptional conservation between immune and epithelial cells of human and porcine intestine, but scRNA-seq studies have so far been limited to only the small intestine.…”
Section: Advantagesmentioning
confidence: 99%
“…In addition to phenotyping a limited number of cellular markers at the protein level to identify proportions of specific IEL populations, high-resolution transcriptional studies suggest pig-to-human similarities of intestinal cells. A recent scRNA-seq study identified conserved expression of several cell type-canonical genes between pig and human epithelial and immune cells that were sparsely expressed in mice ( 198 ). An additional scRNA-seq study defining lymphocyte subsets (including T cells and ILCs) at enhanced resolution also identified transcriptional similarities, similar localization patterns, and conserved inferred functions of lymphocytes from porcine and human ileum ( 57 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, our group has previously established porcine intestinal epitheliocyte (PIE) cells to study the immune responses of swine intestinal epithelial cells via toll-like receptors (TLRs) and reported on their innate immune responses [11]. Considering that the intestinal tract is composed of various cell types, including absorptive epithelial cells, goblet cells, Paneth cells, enteroendocrine cells, BEST4 cells, and intestinal stem cells [12,13], it may be difficult to accurately reproduce the response and function of the intestinal tract when relying solely on cell lines composed of a single cell type. Intestinal organoids, which can self-organize in three dimensions and reproduce the heterogeneity and behavior of the intestinal mucosa, are attractive tools to study in vitro the complex interactions between the different cell types and foreign agents, such as commensal or pathogenic microorganisms [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The next step is to explore the cell-type-dependent biological consequences of trait-associated variants as tissues contain numerous cell types 24 . Although some studies have conducted single-cell/nucleus RNA-seq (scRNA-seq and snRNA-seq) analyses in pigs, they primarily focused on elucidating the cellular heterogeneity and trajectories of lineage speci cation in a limited range of tissue types 25,26,27,28,29,30,31,32 . The cell-type-speci c biological impacts of genetic variants on complex traits by integrating single-cell RNA-sequencing with large-scale pig genetics data still need to be explored.…”
Section: Introductionmentioning
confidence: 99%